2007
DOI: 10.1016/j.juro.2006.08.100
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Skin Collagen Implants to Prevent Anterior Vaginal Wall Prolapse Recurrence: A Multicenter, Randomized Study

Abstract: Our data show that the Pelvicol implant can be easily and readily used to augment and reinforce anterior colporrhaphy. The prolapse recurrence rate was considerably lower in the implant group compared with outcomes in patients treated with simple anterior repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 16 publications
5
59
1
13
Order By: Relevance
“…18 Multiple studies have not demonstrated any difference in surgery with or without meshes. 7,23,24 An advantage, however, was shown in surgery with prosthesis. 25 We used a non-validated questionnaire, but a set of short questions including simple clinical data, limiting the extrapolation of our own results.…”
Section: Discussionmentioning
confidence: 99%
“…18 Multiple studies have not demonstrated any difference in surgery with or without meshes. 7,23,24 An advantage, however, was shown in surgery with prosthesis. 25 We used a non-validated questionnaire, but a set of short questions including simple clinical data, limiting the extrapolation of our own results.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen randomized trials matching our inclusion criteria were published: one in 2006 [5], two in 2007 [6,7], four in 2008 [8][9][10][11], four in 2009 [12][13][14][15] and five in 2010 [16][17][18][19][20]. We added two publications of Nieminen, reporting long-term results of the randomized trial initially written by Hiltunen in 2007 [6,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studied non-absorbable synthetic (NAS) polypropylene implants [6, 8-12, 14, 16, 19-22] and six absorbable biomesh (AB) [5,7,13,15,17,18]. Anatomic results are summed up in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis of randomized studies showed that Pelvicol ® augmentation did not offer better results than anterior repair (RR: 1.3; 95% CI: 0.8-2.2). Only one RCT [91] reported superior results following Pelvicol ® augmentation. This did not change, even when the results of all studies which used any type of biological implant were combined; the use of biological graft material did not appear to improve success rates (RR: 1.34; 95 % CI: 0.97-1.86).…”
Section: Level Of Evidence 3 Grade Of Recommendation Bmentioning
confidence: 99%